Characteristics and outcomes of patients with postoperative Candida versus bacterial mediastinitis: a case-matched comparative study. (18th October 2021) - Moyon, Quentin; Lebreton, Guillaume; Huang, Florent; Demondion, Pierre; Desnos, Cyrielle; Chommeloux, Juliette; Hékimian, Guillaume; Bréchot, Nicolas; Nieszkowska, Ania; Schmidt, Matthieu; Leprince, Pascal; Combes, Alain; et al.
Abstract: OBJECTIVES: Postoperative mediastinitis, a feared complication after cardiac surgery, is associated with high mortality, especially of critically ill patients. Candida species infections are rare and severe, with poorly known outcomes. We conducted a case–control study to describe the characteristics, management and outcomes of patients with postoperative Candida mediastinitis. METHODS: This French, monocentre, retrospective study included all patients with postoperative Candida mediastinitis (January 2003–February 2020) requiring intensive care unit admission. Candida mediastinitis patients (henceforth cases) were matched 1:1 with postoperative bacterial mediastinitis (henceforth control), based on 3 factors during mediastinitis management: age >40 years, cardiac transplantation and invasive circulatory device used. The primary end point was the probability of survival within 1 year after intensive care unit (ICU) admission. RESULTS: Forty cases were matched to 40 controls. The global male/female ratio was 2.1, with mean age at admission 47.9 ± 13.8 years. Candida species were: 67.5% albicans, 17.5% glabrata, 15% parapsilosis, 5.0% tropicalis, 2.5% krusei and 2.5% lusitaniae . The median duration of mechanical ventilation was 23, 68.8% of patients received renal replacement therapy and 62.5% extracorporeal membrane oxygenation support. The probability of survival within the first year after ICU admission was 40 ± 5.5% and was significantly lower for cases than for controls (43 ± 8% vs 80 ± 6.3%, respectively; Log-rank test: P < 0.0001). The multivariable Cox proportional hazards model retained only renal replacement therapy [hazard ratio (HR) 3.7, 95% confidence interval (CI) 1.1–13.1; P = 0.04] and Candida mediastinitis (HR 2.4, 95% CI 1.1–5.6; P = 0.04) as independently associated with 1-year mortality. CONCLUSIONS: Candida mediastinitis is a serious event after cardiac surgery and independently associated with 1-year mortality. Further studies are needed to determine whether deaths are directly attributable to Candida mediastinitis. Abstract : Postoperative mediastinitis is a feared complication after cardiac surgery, with a reported frequency ranging from 0.3% to 2.5% [1] and associated mortality up to 40% [2–5].